Positive and Negative of Gen Z perception on politicians in Indonesia - Armani; Inayatullah, Fadil (Journal of Career and Entrepreneurship, 2024)
The research aims to determine the positive and negative perceptions of Gen Z towards politicians in Indonesia in the mass media or person. The research was conducted on Gen Z aged 17 to 27 at this time, the research sample took the smallest sample, namely 100 respondents. Data analysis was carried out using a qualitative method with stages of determining positive and negative variables, grouping variables and testing again. The assessment uses a range of scales. As a result, Gen Z states that politicians have not fulfilled and violated the requirements they must have as a politician.